PENGGUNAAN BAHASA DAN ISTILAH PEMASARAN DIGITAL DALAM MENINGKATKAN MINAT BELI ONLINE - Sudarsono Sudarsono; Aryati Hamzah; Rita Amini Warastuti (Universitas Bina Taruna Gorontalo, 2023)
This study aims to answer questions about how to use appropriate language and terms to attract consumers' buying interest to make purchases online. This study uses a systematic literature review method. The choice of language and terms in digital marketing is still a problem for most content creators in creating relevant marketing content to attract consumers to make purchases online. Researchers found 14,333 related articles published in 2021 and 2022 then selected and reduced the articles. based on the relevance of the discussion into 168 which were analyzed descriptively qualitatively using the Publish & Perish, Mendeley and VOSviewer applications based on article searches on Google Scholar, Crossreff, PubMed and OpenAlex. Research findings indicate that the use of interesting and valuable language and terms is one of the factors triggers for consumers to make purchases online. Broadly speaking, the choice of language and terms can be categorized into two, namely to target teenage consumers, the language and terms used are more attractive and contemporary in the form of certain slang or idioms. While the language and terms that must be used to target adult consumers, the choice of language and terms that are simpler, not tacky and also not wordy. On the other hand, the impact of the Covid-19 pandemic is still part of consumer activities to make purchases online